Intravenous brain-derived neurotrophic factor reduces infarct size and counterregulates Bax and Bcl-2 expression after temporary focal cerebral ischemia - Schäbitz, Wolf-Rüdiger; Sommer, Clemens; Zoder, Werner; Kiessling, Marika; Schwaninger, Markus; Schwab, Stefan (Stroke, 2000)
Background and Purpose: Pretreatment with intraventricular brain-derived neurotrophic factor (BDNF) reduces ischemic damage after focal cerebral ischemia. In this experiment we studied the effect of intravenous BDNF delivered after focal cerebral ischemia on neurological outcome, infarct size, and expression of proapoptotic and antiapoptotic proteins Bax and Bcl-2, respectively. Methods: With the use of the suture occlusion technique, the right middle cerebral artery in rats was temporarily occluded for 2 hours. Thirty minutes after vessel occlusion, BDNF (300 μg/kg per hour in vehicle; n=12) or vehicle alone (n=13) was continuously infused intravenously for 3 hours. After 24 hours the animals were weighed and neurologically assessed on a 5-point scale. The animals were then killed, and brains underwent either 2,3,5-triphenyltetrazolium chloride staining for assessment of infarct volume or paraffin embedding for morphology and immunohistochemistry (Bax, Bcl-2). Results: Physiological parameters (mean arterial blood pressure, Po2, Pco2, pH, body temperature, glucose) and weight revealed no difference between groups. Neurological deficit was improved in BDNF-treated animals versus controls (P<0.05, unpaired, 2-tailed t test). Mean±SD infarct volume was 229.7±97.7 mm3 in controls and 121.3±80.2 mm3 in BDNF-treated animals (P<0.05, unpaired, 2-tailed t test). Cortical infarct volume was 155.5±78.5 mm3 in the placebo group and 69.9±50.2 mm3 in the BDNF-treated group (P<0.05, unpaired, 2-tailed t test). Subcortical infarct volume was 74.1±30.6 mm3 in the placebo group and 51.1±26.8 mm3 in the BDNF-treated group (P=NS). Bax-positive neurons were significantly reduced in the ischemic penumbra in BDNF-treated animals (P<0.05, unpaired, 2-tailed t test), whereas Bcl-2-positive neurons were significantly increased in this area (P<0.001, unpaired, 2-tailed t test). Conclusions: This study demonstrates a neuroprotective effect of BDNF when delivered intravenously after onset of focal cerebral ischemia. As shown here, one possible mechanism of action of neuroprotection of BDNF after focal ischemia appears to be counterregulation of Bax/Bcl-2 proteins within the ischemic penumbra.